Perito Moreno Glacier dam rupture - A recurrent natural experiment to probe solid-earth elasticity. (December 2020) - Marderwald, Eric Rodolfo; Aragón Paz, Juan Manuel; Richter, Andreas Jörg; Busch, Peter; Malz, Philipp; Mendoza, Luciano Pedro Oscar; Romero, Abelardo; Guerrero, Luz; Hormaechea, José Luis; Connon, Gerardo; Perdomo, Raúl Anibal; Braun, Matthias; et al.
Abstract: The Southern Patagonian Icefield is located in an area with a complex tectonic-rheological structure and is affected by intense glacial-isostatic adjustment and rapid ice retreat. Geodetic observations of loading effects provide information on earth structure. Perito Moreno Glacier repeatedly dams the Brazo Rico and Brazo Sur branches of Lago Argentino. The rupture of the ice dam applies an intense hydrological load signal which results in an elastic response of the solid earth. We present a modelling procedure to predict loading effects in response to water-level changes in Brazo Rico. The output is compared with site displacements observed by GNSS during the 2016 rupture event. Our results show that water-level changes in Brazo Rico exceeding 5 m produce vertical deformations detectable with GNSS observations. A geodetic observation of loading effects at magnitudes similar to those of the maximum historic event in 1956 could provide meaningful constraints on elastic earth models. We discuss consequences for the determination of accurate deformation rates, implications for our understanding of the intense uplift observed at the Southern Patagonian Icefield, and requirements and prospects for obtaining geodetic observations of the loading effects of future rupture events. Highlights: Perito Moreno Glacier dam ruptures cause intense hydrological loading signals. Geodetic observation of loading effects allows validation of elastic earth models. Solid-earth deformation induced by the 2016 outburst is observationally detected.